Digital influences on online shopping among Gen Z in Kedah: the role of social media interaction, online reviews, and price sensitivity / Nuraini Abdullah … [et al.] - Abdullah, Nuraini; Mokhtar, Nuradibah; Abdul Halim, Tisya Farida; Shamsol, Siti Aina Safikah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
influenced by social media interaction, online reviews and price considerations in their purchasing decisions. This study aims to investigate how social media interaction, online reviews, and price considerations impact the purchasing decisions of Gen Z consumers in Kedah, Malaysia. Using a quantitative survey approach, data was collected from 384 Gen Z respondents in Kedah, focusing on their social media usage patterns, reliance on online reviews and responses to pricing considerations. The results revealed a significant positive correlation between active social media engagement, positive perception of online reviews, and price consideration among Gen Z consumers in Kedah. In contrast, regression analysis revealed social media as the strongest predictor in influencing this demographic’s online shopping behaviour. The study provides insight on how digital platforms would affect consumer behaviour, especially among Gen Z. It highlights the need for businesses to understand and align their marketing strategies with the unique preferences of this Gen Z. This approach will enhance customer engagement at the exact times and help companies to stay relevant and competitive in the ever-evolving online marketplace. However, the study has a geographical limitation and only relies on self-reported data, which may give a biased response. Future research should expand to include diverse regions, adding additional variables for deeper insights. The findings underscore digital platforms' role in shaping Gen Z consumer behaviour. They also highlight opportunities for businesses to fine-tune marketing strategies that suit this tech-savvy demographic, increasing their competitiveness in the online marketplace.